Lyophilized allogeneic bone tissue as an antibiotic carrier - Coraça-Huber, Débora C. (Cell Tissue Bank, 2016)
The rising number of primary joint replacements worldwide causes an increase of revision surgery of endoprostheses due bacterial infection. Revision surgery using non-cemented implants seems beneficial for the long-term outcome and the use of antibiotic-impregnated bone grafts might control the infection and give a good support for the implant. In this study we evaluated the release of antibiotics from fresh-frozen and lyophilized allogeneic bone grafts. Lyophilized bone chips and fresh frozen bone chips were mixed with gentamicin sulphate, gentamicin palmitate, vancomycin, calcium carbonate/calcium sulphate impregnated with gentamicin sulphate, and calcium carbonate/calcium sulphate bone substitute material impregnated with vancomycin. The efficacy of each preparation was measured by drug release tests and bacterial susceptibility using B. subtilis, S. aureus and methicillin-resistant Staphylococcus aureus. The release of gentamicin from lyophilized bone was similar to the release rate from fresh frozen bone during all the experimental time. That fact might be related to the similar porosity and microstructure of the bone chips. The release of gentamicin from lyophilized and fresh frozen bone was high in the first and second day, decreasing and keeping a low rate until the end of the second week. Depending on the surgical strategy either polymethylmethacrylate or allogeneic bone are able to deliver sufficient concentrations of gentamicin to achieve bacterial inhibition within two weeks after surgery. In case of uncemented revision of joint replacements allogeneic bone is able to deliver therapeutic doses of gentamicin and peak levels immediately after implantation during a fortnight. The use of lyophilized and fresh frozen bone allografts as antibiotic carriers is recommended for prophylaxis of bone infection.